Point mutation in the cytoplasmic domain of the neutrophil p22-phox cytochrome b subunit is associated with a nonfunctional NADPH oxidase and chronic granulomatous disease. - Dinauer, M C (1991)
Chronic granulomatous disease (CGD) is a congenital disorder in which phagocytes cannot generate superoxide (O2-) and other microbial oxidants due to mutations in any one of four components of the O2(-)-generating complex, NADPH oxidase. We report here a female CGD patient in whom a missense mutation in one of these components, the p22-phox subunit of the neutrophil membrane cytochrome b [where phox indicates phagocyte oxidase (used to designate protein components of the phagocyte NADPH oxidase)] results in a nonfunctional oxidase and failure of neutrophils to produce O2- in response to phorbol 12-myristrate 13-acetate. Cytochrome b in the patient's neutrophils was normal in appearance and abundance as determined by visible spectroscopy and by immunoblots of the gp91 and p22 subunits. However, the neutrophil plasma membranes were devoid of activity in the cell-free oxidase activation system, whereas the cytosol functioned normally. We postulated that the patient was homozygous for a mutation in p22 that results in the synthesis of normal levels of a nonfunctional cytochrome b. A single-base substitution (C----A) was found in the patient's mononuclear cell p22-phox cDNA that predicts a nonconservative Pro----Gln substitution at residue 156. The same mutation was also identified in all clones sequenced from patient genomic DNA, demonstrating homozygosity for the mutant allele. An antipeptide antibody against p22 residues 153-164 was found to bind only to permeabilized neutrophils, indicating that the mutation occurs in a cytoplasmic domain. These studies establish that this domain of p22-phox is cytoplasmic and that mutations in this region can have profound effects on cytochrome b function.